Motives for Profit Sharing: A Study of Canadian Chief Executive Officers - Long, Richard (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1997)
This study seeks to explain why companies do or do not introduce employee profit sharing, through a telephone survey of chief executive officers at 626 Canadian companies. In addition to examining some of the usual contextual variables, this study goes beyond previous work by directly questioning CEOs about their motives for adopting or not adopting profit sharing, and by including managerial philosophy as a possible factor in their decision-making process. Results indicated that managerial philosophy and company size were the two key predictors of incidence of profit sharing. However, the firms most likely to adopt profit sharing in the future were those experiencing a high growth in sales coupled with a low growth in employees. Surprisingly, unionization was not related to either présence of, or intention to implement, profit sharing.